Understanding the intention-behavior gap towards aerobic exercise in persons with multiple sclerosis - Argie, Andrew Robert (My University, 2025)
Abstract Background: Despite strong intentions to engage in regular aerobic exercise, persons with Multiple Sclerosis (PwMS) frequently encounter a significant intention-behavior gap, limiting potential health benefits from sustained aerobic exercise. While existing research has addressed general barriers to exercise in this population, further examination of psychological processes that contribute to this gap is necessary. This study applied the Multi-Process Action Control (M-PAC) framework to identify reflective, regulatory, and reflexive predictors related to the intention-behavior gap toward aerobic exercise in PwMS. Methods: Using a cross-sectional e-survey, 395 PwMS were recruited through a regional healthcare system (Stormont Vail; n = 88), an online participant platform (Prolific; n = 274), and online discussion forms (n = 33). Participants completed a 48-item questionnaire assessing demographics, clinical variables, and M-PAC constructs (reflective, regulatory, reflexive processes). Individuals were classified into three action control profiles: Successful Intenders (SI), Unsuccessful Intenders (USI) and Non-intenders. Hierarchical multinomial logistic regression analyses identified predictors influencing intention formation and successful adherence (action control) to aerobic exercise guidelines. Results: The intention formation model represented strong fit (R² = 0.58) and classified younger age (OR = 0.966; p = .011), positive affective judgements (OR = 1.203, p < .001), higher perceived capability (OR = 1.235, p = .002), and greater perceived opportunity (OR = 1.258 p = .029), as significant predictors of intention formation. The action control model represented moderate fit (R² = 0.23) and classified strong exercise identity (OR = 1.140, p = .004) and lower PDDS scores (OR = 0.849, p = .032) as significant predictors of PwMS successfully meeting MS aerobic exercise training guidelines. Additionally, proactive regulation (OR = 1.067, p = .017) and reactive regulation (OR = 1.076, p = .024) were significant predictors in earlier action control models, but lost significance once reflexive processes were accounted for. Conclusions: Findings from this study highlight potential processes important for forming exercise intentions among PwMS, including positive affective judgements, perceived capability, and perceived opportunity. Additionally, directly enhancing exercise identity may be beneficial for bridging the intention-behavior gap, however, development of behavioral regulation is essential. These applications may be beneficial for guiding interventions to increase sustained aerobic exercise adherence in PwMS long-term.
Keywords: Kinesiology; Multiple sclerosis; Intention behavior; Exercise behavior